Cancellation of Homologated Peace by Creditors: (Analysis of the Legal Standing of Cooperative Members as PKPU Applicants in the Commercial Court Decision at the Semarang District Court Number 1/Pdt.Sus-Pembatalan Perdamaian/2023/ PN Niaga Smg jo. Number 43/Pdt.Sus-PKPU/2020/PN Niaga Smg) - Gisymar, Najib; Kusuma Dewi, Elya (Jurnal Legisci, 2025)
Background. The Sharia Savings and Loan Cooperative and Financing (KSPPS) as the Debtor in the Suspension of Debt Payment Obligations case Number 43/Pdt.Sus-PKPU/2020/PN Niaga Smg (PKPU 43/2020/Smg), submitted a peace proposal to the Creditors and was eventually approved by the Creditors, making it binding and must be fulfilled by the Debtor. Aim. This research examines the legal considerations of judges regarding the rights of KSPPS members as Creditors who file for annulment of the Homologation Agreement agreed upon by the Creditors and Debtor. Methods.This paper is the result of research using a normative juridical approach. Legal research based on the study of the Cancellation Decision of PKPU 1/2023/Smg, linked to legal norms and regulations. This research is descriptive-analytical in nature. Data analysis was conducted using qualitative analysis methods, related to the rejection of the annulment of the Peace Agreement/Homologation by the Assembly, with the consideration that the meeting of members could bankrupt the Cooperative. Result. KSPPS is considered to have failed to fulfill the contents of the Homologation, thus the Creditors have the right to file for the annulment of the Homologation through the commercial court proceedings mechanism and registered in the case register Number 1/Pdt.Sus-Pembatalan Perdamaian/2023/PN Niaga Smg ("PKPU No. 1/2023/Smg"). However, the annulment of the Homologation was rejected by the first-instance court and cassation because the Cooperative can only be declared bankrupt if approved by the Members' Meeting. Conclusion. The Supreme Court must be able to bridge the differences in interpretation by issuing guidelines for interpreting the provisions of Article 291 paragraph (2) of the K-PKPU Law, thereby achieving legal certainty. Implication. This research is useful as an example of overcoming the case of reconciliation of cooperative creditors and canceling agreements.